Culture, Labor Supply, and Fertility Across Immigrant Generations in the United States. Issue 1 (2nd January 2020) - Muchomba, Felix M.; Jiang, Nan; Kaushal, Neeraj
Abstract : Recent immigration to the United States and other developed nations has increasingly been from countries that have relatively traditional gender norms. This study uses data from the Current Population Survey for 2000–14 to investigate how source-country gender norms influence the labor supply and fertility of married women across immigrant generations in the US. It finds that immigrants' and descendants' labor supply and fertility are associated with the female-to-male labor force participation ratio and total fertility rate in the source country; importantly, the association declines across successive generations. Husbands' source-country characteristics are also associated with the labor supply and fertility of immigrant women. These findings indicate evolution and assimilation of traditional gender norms in the long run.